Ronan Bouroullec - Triptyque Triptyque - Bethenod, Martin 1966- (Éditions 7L, 2024)
In 2023, as part of the rich programme celebrating its centenary, the villa Noailles has invited Ronan Bouroullec to present three exhibitions: Dessins quotidiens (Daily Drawings) at the Hôtel des Arts in Toulon, Les mains à l'argile (Hands to Clay) at the Galerie du Canon and Productions récentes (Recent Productions) at the villa Noailles itself. The invitation took the form of a triptych resonating with the world of Ronan Bouroullec, where the effects of unfolding, perspective and the organisation of visual planes occupy a central place. The graphic design of this book is an extension of this. For the first time, Ronan Bouroullec's three intertwined daily practices are brought together in a single work: drawing, clay--through his ceramic sculptures, vases, facing tiles and bas-reliefs--and also his latest proposals for object design and in situ projects, including the renovation of the Saint-Michel chapel in Brasparts
Impressum: Ce livre a été publié à l'occasion des expositions "Dessins quotidiens" à l'Hôtel des Arts TPM du 4 mars au 29 avril 2023, "Les mains à l'argile" à la Galerie du Canon de Toulon du 23 juin au 5 novembre 2023 et "Productions récentes" à la villa Noailles du 24 juin au 3 septembre 2023, dans le cadre de Design Parade Hyères - 17e Festival international de design
Keywords: Bouroullec, Ronan -- 1971-; Bouroullec, Ronan / 1971- / Exhibitions; Ausstellungskatalog -- Hôtel des Arts - Centre d'Art TPM -- 04.03.2023-29.04.2023 -- Toulon; Ausstellungskatalog -- Galerie du Canon -- 23.06.2023-05.11.2023 -- Toulon; Ausstellungskatalog -- Villa Noailles -- 24.06.2023-03.09.2023 -- Hyères; Bildband